Spectrophotometric Determination of Valacyclovir in Pharmaceutical Formulation - SRINU BABU, G.; SARAT BABU, I.; KIRAN KUMAR, N.; YUGANDHAR, N.M.; A.I. RAJU, CH. (Asian Journal of Chemistry, 2010)
A Simple, sensitive, spectrophotometric method in UV region has been developed for the determination of valacyclovir in bulk and tablet dosage forms. Valacyclovir is a new antiviral drug, which shows maximum absorbance at 274 nm with apparent molar absorpitivity of 2.69167 × 104 L/molcm. Beer's law was obeyed in the concentration range of 5-50 μg/mL. Results of the analysis were validated statistically and by recovery studies.